Hardships faced by the trans population in the access to health services: an integrative literature review (Research, Society and Development, 2022)
The access to health services is a constitutional right of all people. This article aimed to carry out an integrative review about the difficulties faced by the trans population to access health services. 15 articles, published from 2012 to 2021, were found in the databases Índice Bibliográfico Español en Ciencias de la Salud (IBECS), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), and Scientific Electronic Library Online (SciELO). To discuss the results, four categories of analysis were created: Overview of Legislation Milestones on the Rights of the Trans Population; Stigma and Discrimination Against the Trans Population; The Binary and Biological Logic that Considers Transsexuality as a Pathology and the Lack of Effective Health Services and Professional Practices in the Attention to the Trans Population. We concluded that rejecting the plural experiences of trans people in the access to health services and pathways hinders the qualified assistance from professionals and institutions, be they public or private, putting this population at risk and making preventive actions targeted at integral healthcare more difficult to achieve. We argue that it is necessary to create practices in health in both the public sphere and society as a whole, guaranteeing rights and reducing prejudice.